2012
DOI: 10.1128/jvi.00118-12
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of the Superfamily 1 Helicase from Tomato Mosaic Virus

Abstract: The genomes of the Tomato mosaic virus and many other plant and animal positive-strand RNA viruses of agronomic and medical importance encode superfamily 1 helicases. Although helicases play important roles in viral replication, the crystal structures of viral superfamily 1 helicases have not been determined. Here, we report the crystal structure of a fragment (S666 to Q1116) of the replication protein from Tomato mosaic virus. The structure reveals a novel N-terminal domain tightly associated with a helicase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 52 publications
1
36
0
Order By: Relevance
“…We recently determined a crystal structure for the helicase domain of ToMV 130K protein (residues 666 to 1116), which consists of a C-terminal helicase core containing two RecA folds and an N-terminal accessory domain (49). Yeast two-hybrid experiments designed in light of the structure information suggested that ARL8 interacts with the N-terminal accessory domain and TOM1 interacts with both the accessory domain and the helicase core (49).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We recently determined a crystal structure for the helicase domain of ToMV 130K protein (residues 666 to 1116), which consists of a C-terminal helicase core containing two RecA folds and an N-terminal accessory domain (49). Yeast two-hybrid experiments designed in light of the structure information suggested that ARL8 interacts with the N-terminal accessory domain and TOM1 interacts with both the accessory domain and the helicase core (49).…”
Section: Discussionmentioning
confidence: 99%
“…Yeast two-hybrid experiments designed in light of the structure information suggested that ARL8 interacts with the N-terminal accessory domain and TOM1 interacts with both the accessory domain and the helicase core (49). Moreover, the reporter activity in the yeast two-hybrid experiment was much stronger between ARL8 and the accessory domain alone than between ARL8 and the full-length helicase domain polypeptide, suggesting that conformational changes in the 130K protein to expose the ARL8-binding site are associated with the process of complex formation (49). On the other hand, the mutation sites of the resistance-breaking ToMV mutants are located on the surface of the helicase core that is opposite the surface where the accessory domain is located.…”
Section: Discussionmentioning
confidence: 99%
“…30 Crystal structure of the helicase domain of ToMV superfamily 1 helicase solved recently has provided key insight into the helicase region required for binding to Arl8 and TOM1. 53 …”
Section: Arl8b Regulates Phagosome-lysosome Fusion and Microbial Pathmentioning
confidence: 99%
“…The amino acid changes found in Tm-1 resistance-breaking mutants locate at the helicase domain of ToMV replication proteins (ToMV-Hel) and decrease the affinity of Tm-1 for the replication proteins (12). We recently determined a crystal structure of ToMV-Hel (residues S666-Q1116 of the replication proteins) (15). ToMV-Hel contains two canonical RecA-like α/β domains (1A and 2A), which form the helicase core, and a structurally unique N-terminal domain.…”
Section: Significancementioning
confidence: 99%
“…ToMV-Hel contains two canonical RecA-like α/β domains (1A and 2A), which form the helicase core, and a structurally unique N-terminal domain. The positions of mutations in Tm-1 resistance-breaking mutants have been mapped to the surface of the molecule (15).…”
Section: Significancementioning
confidence: 99%